Pinguicula simulans (Lentibulariaceae), a new species from Nuevo León, Mexico - Zamudio, Sergio; Salinas-Rodríguez, María Magdalena; Quirino-Olvera, Ricardo; Hernández-Rendón, Julián (Phytotaxa, 2019)
Pinguicula simulans (Lentibulariaceae), a new species endemic to Sierra Madre Oriental, is described and illustrated from plants collected at Potrero Redondo, municipality of Santiago, Nuevo Léon, Mexico. Its flowers are similar to those of P. gracilis and the new species therefore belongs to Pinguicula subg. Temnoceras, sect. Microphyllum. It differs from other species in the section by the spatulate winter leaves, which are longer than wide, with a slightly recurved apex. In addition, it is distinguished by the long spatulate, ascendant or diffuse, recurved, summer leaves, which form a loose rosette, and by the calyx that has glandular pubescence on both surfaces.